The State of the nations: constraints on development in independent Africa - Lofchie, Michael F. (Berkeley : University of California Press, 1971)
This is a collection of essays that examine political experience of the countries of independent Africa must be understood in terms of constraints. Divided into three parts, the first contains two chapters on general perspectives while the second offers eight case studies concerned with five individual countries-Senegal, Ghana, Tanzania, Ivory Coast, and Uganda. The third part has three chapters devoted to prospects for future development.
Bibliography: p. [287]-293.
lje 16/10/18
Loans
Keywords: Economic development; Economic growth; Africa